INNOVATIVE SERVICES OF UNIVERSITY LIBRARY AND OPPORTUNITIES OF OPEN ACCES - Shytikova, Tetiana M.; Chumak, Natalya V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article deals with possibilities of оpen access that contribute to development of science and society in general. On the example of scientific and technical library are considered digital services that provide to university scientists for ensure of information needs of users and promotion the results of their scientific research in global scientific and educational space.